2008
DOI: 10.1080/10428190801935752
|View full text |Cite
|
Sign up to set email alerts
|

Anti proliferative activity of ELACYT™ (CP-4055) in combination with cloretazine (VNP40101M), idarubicin, gemcitabine, irinotecan and topotecan in human leukemia and lymphoma cells

Abstract: This study evaluated combination drug partners for CP-4055, the C18:1 D9,trans unsaturated fatty acid ester of cytarabine in HL-60 and U937 cells. Growth inhibition was assessed by ATP assay and drug interaction by the combination index and three dimensional methods. Synergy was observed in HL-60 cells for simultaneous combinations of CP-4055 with gemcitabine, irinotecan and topotecan, while combinations with cloretazine (VNP40101M) and idarubicin were additive. In U937 cells, synergy was observed with gemcita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…A currently bourgeoning research area for cancer treatment is the drug combination method (Adams et al, 2008;Chou et al, 2006;Dicko et al, 2010;Feldman et al, 2007;Lee, 2012). Recent investigations documented the efficacy of combining cisplatin with other drugs, providing a rational basis for the design of new well-tolerated platinum-based treatment in cancer chemotherapies (Facy et al, 2011;Jiang et al, 2011;Rattan et al, 2011).…”
Section: Introductionmentioning
confidence: 97%
“…A currently bourgeoning research area for cancer treatment is the drug combination method (Adams et al, 2008;Chou et al, 2006;Dicko et al, 2010;Feldman et al, 2007;Lee, 2012). Recent investigations documented the efficacy of combining cisplatin with other drugs, providing a rational basis for the design of new well-tolerated platinum-based treatment in cancer chemotherapies (Facy et al, 2011;Jiang et al, 2011;Rattan et al, 2011).…”
Section: Introductionmentioning
confidence: 97%
“…Recent studies by our laboratory and others have shown that the therapeutic activity of drug combinations is often drug ratio dependent, where synergistic or antagonistic interactions occur when tumors are exposed to different drug/ drug ratios (12)(13)(14)(15). Thus, the full benefit of combination chemotherapy may not be realized in vivo unless the ratios of the drugs are carefully controlled and maintained to avoid exposure of tumor cells to antagonistic drug ratios.…”
Section: Introductionmentioning
confidence: 99%
“…Drug interaction was assessed with ATP-based growth inhibition assays by combination index and combination effect endpoints using published methods of Chou [11] and Kanzawa [26], respectively, as reported previously [6, 37]. …”
Section: Methodsmentioning
confidence: 99%